2018
DOI: 10.1016/j.rser.2017.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Future views on waste heat utilization – Case of data centers in Northern Europe

Abstract: overview of upcoming data center projects where waste heat is utilized is presented. Especially in Finland data center operators are planning to reuse waste heat in district heating. However, business models between the district heating network operator and data center operator are often not transparent. The implications of economics and emissions on waste heat utilization in district heating were analyzed through life cycle assessment. Currently the biggest barriers for utilizing waste heat are the low qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 31 publications
(74 reference statements)
0
79
0
Order By: Relevance
“…It has also been suggested that small-scale distributed servers could be used as heat sources in individual apartments (Woodruff et al 2013), where temperatures of 25 to 35°C would be sufficient to meet heating demands. On a larger scale, utilizing waste heat in district heating systems is becoming common in Northern Europe (Wahlroos et al 2018;Davies et al 2016). For use in district heating, low-grade heat must be upgraded with heat pumps in order to reach temperatures of 75 to 120°C for distribution in district heating networks, although fourth-generation district heating can be run with supply temperatures of 45 to 55°C (Wahlroos et al 2018;Lund et al 2014).…”
Section: Heat Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that small-scale distributed servers could be used as heat sources in individual apartments (Woodruff et al 2013), where temperatures of 25 to 35°C would be sufficient to meet heating demands. On a larger scale, utilizing waste heat in district heating systems is becoming common in Northern Europe (Wahlroos et al 2018;Davies et al 2016). For use in district heating, low-grade heat must be upgraded with heat pumps in order to reach temperatures of 75 to 120°C for distribution in district heating networks, although fourth-generation district heating can be run with supply temperatures of 45 to 55°C (Wahlroos et al 2018;Lund et al 2014).…”
Section: Heat Integrationmentioning
confidence: 99%
“…Several data centres are currently developing this concept in Scandinavia (Wahlroos et al 2018). Stockholm Data Parks (2019) is an example where several data centres are co-located around a central heat pump station that increases the temperature of the waste heat and supplies the district heating network.…”
Section: Heat Integrationmentioning
confidence: 99%
“…Increase of cloud computation demand and capability results in growing hyperscale cloud servers that consume a huge amount of energy. In 2010, data centers accounted for 1.1-1.5% of the world's total electricity consumption [2], with a spike to 4% in 2014 [3] raised by the move of localized computing to cloud facilities. It is anticipated that the energy consumption of data centers will double every five years [4].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of recovering waste heat from data centers was investigated by the authors of [18][19][20], who highlighted the high energy consumption associated with cooling systems in data centers and indicated how recovering low-grade waste heat from these systems can increase the operating efficiency of data centers. The authors of [19] showed how a data center can be cooled by air, liquid or a combination of the two (hybrid cooling).…”
Section: Data Centersmentioning
confidence: 99%